Interplay between mammalian heat shock factors 1 and 2 in physiology and pathology - Roos-Mattjus Pia; Sistonen Lea (WILEY, 2025)
The heat-shock factors (HSFs) belong to an evolutionary conserved family of transcription factors that were discovered already over 30 years ago. The HSFs have been shown to a have a broad repertoire of target genes, and they also have crucial functions during normal development. Importantly, HSFs have been linked to several disease states, such as neurodegenerative disorders and cancer, highlighting their importance in physiology and pathology. However, it is still unclear how HSFs are regulated and how they choose their specific target genes under different conditions. Posttranslational modifications and interplay among the HSF family members have been shown to be key regulatory mechanisms for these transcription factors. In this review, we focus on the mammalian HSF1 and HSF2, including their interplay, and provide an updated overview of the advances in understanding how HSFs are regulated and how they function in multiple processes of development, aging, and disease. We also discuss HSFs as therapeutic targets, especially the recently reported HSF1 inhibitors.